2012
DOI: 10.1371/journal.pone.0047009
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Contributions to Object Recognition: Evidence from Rapid Perceptual Learning

Abstract: The present study investigated implicit and explicit recognition processes of rapidly perceptually learned objects by means of steady-state visual evoked potentials (SSVEP). Participants were initially exposed to object pictures within an incidental learning task (living/non-living categorization). Subsequently, degraded versions of some of these learned pictures were presented together with degraded versions of unlearned pictures and participants had to judge, whether they recognized an object or not. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…The source modeling results showed a distributed network of cortical regions underlying the perception of bodies and chairs including parietal, temporal and occipital areas. These localizations are in line with previous results using SSVEP in object representations (Kaspar et al 2010;Martens and Gruber 2012;Martens et al 2012b), as well as with imaging studies which showed the pivotal role of the lateral occipital complex in object recognition (Kourtzi and Kanwisher 2000;Grill-Spector et al 2001). According to Tanaka (2003), familiar stimuli consist of various "critical features" that are more complex than simple features such as orientation or color (which are also contained in unfamiliar images), but at the same time are not specific enough to represent the objects in their whole.…”
Section: Discussionsupporting
confidence: 92%
“…The source modeling results showed a distributed network of cortical regions underlying the perception of bodies and chairs including parietal, temporal and occipital areas. These localizations are in line with previous results using SSVEP in object representations (Kaspar et al 2010;Martens and Gruber 2012;Martens et al 2012b), as well as with imaging studies which showed the pivotal role of the lateral occipital complex in object recognition (Kourtzi and Kanwisher 2000;Grill-Spector et al 2001). According to Tanaka (2003), familiar stimuli consist of various "critical features" that are more complex than simple features such as orientation or color (which are also contained in unfamiliar images), but at the same time are not specific enough to represent the objects in their whole.…”
Section: Discussionsupporting
confidence: 92%
“…Localization information has been drawn largely from fMRI based studies, whilst time-resolved EEG and MEG has provided temporal information about processing of disambiguated images. Recognition induced effects have been found at 120 ​ms ( Urakawa et al., 2015 ; Samaha et al., 2016 ), at the peak of N170 component ( Jemel et al., 2003 ), around 200 ​ms ( Goffaux et al., 2004 ), after 250 ​ms ( Minami et al., 2014 ), after 500 ​ms ( Flounders et al., 2019 ), after 750 ​ms ( Martens et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various neuroimaging techniques have been used in these experiments: positron-emission tomography (PET) ( Dolan et al., 1997 ), functional magnetic resonance imaging (fMRI) ( Hegdé and Kersten, 2010 ; Ludmer et al., 2011 ; Gorlin et al., 2012 ; Van Loon et al., 2016 ; González-García et al., 2018 ), electroencephalography (EEG) ( Jemel et al., 2003 ; Goffaux et al., 2004 ; Martens et al., 2012 ; Minami et al., 2014 ; Samaha et al., 2016 ), MEG ( Urakawa et al., 2015 ; Flounders et al., 2019 ), repetitive transcranial magnetic stimulation (rTMS) ( Giovannelli et al., 2010 ) and even single neuron recording in a monkeys ( Tovee et al., 1996 ). In these studies, recognition effects were found in low-level visual areas ( Gorlin et al., 2012 ; Van Loon et al., 2016 ), ventral occipito-temporal regions ( Tovee et al., 1996 ; Dolan et al., 1997 ; Gorlin et al., 2012 ; Hegdé and Kersten, 2010 ; Martens et al., 2012 ; Urakawa et al., 2015 ; Van Loon et al., 2016 ), parietal cortex ( Dolan et al., 1997 ; Giovannelli et al., 2010 ; Minami et al., 2014 ; González-García et al., 2018 ), and frontal cortex ( Martens et al., 2012 ; González-García et al., 2018 ). Localization information has been drawn largely from fMRI based studies, whilst time-resolved EEG and MEG has provided temporal information about processing of disambiguated images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaspar et al [13] suggested that SSVEPs showed different amplitudes between familiar and unfamiliar objects, and the effect was dependent upon SSVEP frequencies [13]. Martens et al [14] suggested that SSVEPs are sensitive to implicit mechanisms involving object recognition [14]. Then, are SSVEPs modulated by the cognitive state, even though seeing the same images?…”
Section: Introductionmentioning
confidence: 99%